2007
DOI: 10.1159/000111703
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Interferon-Based Therapy for Chronic Hepatitis C

Abstract: Hepatitis C virus infection frequently causes chronic liver disease leading to cirrhosis and hepatocellular carcinoma (HCC) and has become the main indication for liver transplantation. Interferon (IFN)-based therapy has been used in the treatment of chronic hepatitis C (CHC) for viral clearance. Several earlier studies showed long-term beneficial effects of IFN monotherapy in reducing the progression of cirrhosis, hindering HCC development, and prolonging survival among both sustained virological responders a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 90 publications
0
32
0
Order By: Relevance
“…Failure to achieve an SVR to IFN-based therapies, and preexisting advanced hepatic fibrosis and/or cirrhosis, are major predictors of HCC [6,23,25,39,40]. In the present study, SVR emerged as an independent risk factor for the development of HCC, while non-SVR was not.…”
Section: Development Of Hccmentioning
confidence: 41%
“…Failure to achieve an SVR to IFN-based therapies, and preexisting advanced hepatic fibrosis and/or cirrhosis, are major predictors of HCC [6,23,25,39,40]. In the present study, SVR emerged as an independent risk factor for the development of HCC, while non-SVR was not.…”
Section: Development Of Hccmentioning
confidence: 41%
“…SVR is usually considered synonymous with cure and associated with decreasing cirrhosis complications [16], [26], [33], [34], though the data supporting this assumption remain inconclusive. To date, no randomized, controlled trials of IBT have demonstrated a beneficial impact on overall mortality, liver specific mortality or development of HCC, and most of the evidence in favor of IBT is inferred from data of highly selected patients, clinical trials, or cirrhotic patients in tertiary medical centers [7], [9], [11], [12], [14][16], [18], [19], [22]–[24], [26], [33], [35].…”
Section: Discussionmentioning
confidence: 99%
“…HCC occurrence/recurrence is not an endpoint (101) Study mistype (not RCT or cohort study) (31) No anti-viral therapy (9) Use of unapproved anti-viral agent ( our review criteria used conventional interferon (natural or recombinant) and the cumulative evidence indicated benefit of adjuvant interferon therapy in terms of improved RFS. The meta-regression analysis indicated that a lower percentage of patients with multiple tumors and the use of ablation therapy were the most important independent predictors for better treatment efficacy.…”
Section: Causes Of Exclusion (No Of Abstracts)mentioning
confidence: 99%
“…Newer anti-viral regimens, including nucleoside analogs, pegylated interferon and interferon-nucleoside combination therapy, can produce higher virological and biochemical responses [29,30]. The improved virological responses have been found to be associated with reduced HCC development in patients with chronic HCV infection, but data on long-term efficacy of these new regimens for the prevention of HCC recurrence after curative HCC therapy is lacking [31,32].…”
Section: Causes Of Exclusion (No Of Abstracts)mentioning
confidence: 99%